PEMANFAATAN LIMBAH FLY ASH PLTU CIREBON SEBAGAI MATERIAL ALTERNATIF FILLER PADA CAMPURAN AC - WC : PEMANFAATAN LIMBAH FLY ASH PLTU CIREBON SEBAGAI MATERIAL ALTERNATIF FILLER PADA CAMPURAN AC - WC - Muhammad Aulia Rayhan; Shinta Novriani (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
The ongoing operation of coal-fired power plants poses an environmental challenge due to the massive accumulation of fly ash. This experimental study evaluates the viability of utilizing industrial waste fly ash from PLTU Cirebon as an alternative filler in Asphalt Concrete - Wearing Course (AC-WC) road pavements. Laboratory specimens were prepared using a standard Marshall design framework with varying fly ash filler concentrations of 0%, 2%, and 4% by weight of the aggregate blend. Volumetric evaluations and structural stability tests were systematically conducted to assess overall mix performance. Empirical results indicate that incorporating fly ash significantly optimizes the internal structure of the asphalt. The reference mix (0% fly ash) exhibited a Marshall stability of 1394.9 kg, which experienced a controlled reduction to 1353.7 kg at 2% substitution and 1166.2 kg at 4% substitution, while remaining well above the minimum standard of 800 kg. Air voids (VIM) decreased consistently from 3.87% to 3.80% and 2.55% for the 0%, 2%, and 4% blends, respectively. Notably, the 4% dosage fell short of the mandatory 3% minimum threshold, introducing a risk of pavement bleeding. Meanwhile, the moisture susceptibility analysis revealed that the 2% fly ash mix achieved an optimal retained stability index of 97.97%, outperforming the control group. Based on a holistic analysis of physical and volumetric performance criteria, a 2% fly ash content is established as the ideal balance, fulfilling all Bina Marga regulatory codes while promoting eco-friendly, circular infrastructure development.